2001
DOI: 10.1088/0264-9381/18/17/101
|View full text |Cite
|
Sign up to set email alerts
|

Coherent degenerate dark matter: a galactic superfluid? 1

Abstract: Dark matter comprising a Bose-Einstein condensate (BEC) forms structures of the size of its coherence length, as determined by equilibrium between quantum pressure and gravitational attraction. This is also the core size of quantum vortices in a BEC superfluid. From the density and rotation curve of the Andromeda Galaxy (M31) we estimate the particle mass, particle density, coherence length, critical temperature, critical angular frequency, and vortex line density of the dark matter condensate composing the ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 13 publications
2
29
0
Order By: Relevance
“…Similar ideas were independently investigated by many authors [23,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][40][41][42][43][44][45]. For example, a model with m = 0 was suggested in [27], which has a stability issue.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Similar ideas were independently investigated by many authors [23,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][40][41][42][43][44][45]. For example, a model with m = 0 was suggested in [27], which has a stability issue.…”
mentioning
confidence: 68%
“…Guzman and Matos et al [46,47] extensively studied various astrophysical aspects of the SFDM. Other attempts are based, for example, on a non-minimal coupling [28], quintessence [29,48], Repulsive DM [30], fluid DM [32], nontopological soliton [33], cosh potential [35,36], and ULA [34,37,38] among many [39][40][41][42][43][44]49]. The BEC nature of this DM was extensively studied in [9,23,50] by Harko, Chavanis and their colleagues.…”
mentioning
confidence: 99%
“…Similar models are regarded earlier [29] for a Bose-Einstein condensate whose properties intimately related to the superfluidity and superconductivity. In particular it is found that the coherence length of the cosmic Bose-Einstein condensate is equal to the Jeans wavelength.…”
Section: Robertson-walker Metricsmentioning
confidence: 85%
“…The second term in (29) is found using the explicit expression for g i j and decomposition (17). Then the balance Eq.…”
Section: Balance Equations Of Phonon Gasmentioning
confidence: 99%
“…We approach a state described by the Bose-Einstein statistics and likely present in the regions of the Universe shielded from the temperature of microwave background radiation of the Big Bang, which currently is 2.725 K. Such shielded states exist at the edge of the black holes or gravastars (Mazur and Mottola, 2004). Gravastars are quark stars representing a gravitational version of Bose-Einstein condensate, which is all composed of an identical wave function (Silverman and Mallett, 2001). It consists of particles created in pairs out of the vacuum near the edge of the black hole being the place where the four fundamental forces come together (Garay, 2002).…”
Section: Coherent States and Computationmentioning
confidence: 99%